The reduction of fat deposition in broiler chickens fed diet containing modified rice bran tempeh - Santoso, U.; Fenita, Y.; Kususiyah, K.; Fahmi, Z. O.; Restu, A. (Diponegoro University, 2024)
The aim of this study was to assess the impact of modified rice bran tempeh on performance, carcass quality, organoleptic properties, fat deposition, and nutritional meat composition in broiler. This research used a completely randomized design. Two hundred broilers (a male to female ratio of 1:1) were divided into 4 treatment groups with 5 replications for each treatment, as follows: P1 = Feed without modified rice bran tempeh; P2 = Feed with 20% rice bran tempeh; P3 = Feed with 20% modified rice bran tempeh; and; P4 = Feed with 25% modified rice bran tempeh. The experimental results showed that all treatment groups had similar performance. The treatments significantly reduced (P<0.05) abdominal fat and total fat deposition. In addition, the treatments also significantly reduced meat fat and ash content (P<0.01), but it significantly increased (P<0.01) moisture contents. It was concluded that feeding 20% or 25% modified rice bran tempeh reduced meat fat content and fat deposition without reducing broiler performance.